catena-Poly[[bis(ethylenediamine)copper(II)]-μ-sulfato] - Lutz, Martin (International Union of Crystallography, 2010)
In the title compound, [Cu(SO(4))(C(2)H(8)N(2))(2)](n), the Cu, S and two O atoms lie on a mirror plane. The Cu atom is in a distorted octahedral environment and the ethylenediamine ligand is in a gauche conformation. The sulfate dianion is bridging, forming a one-dimensional chain. A two-dimensional net parallel to (001) is generated by N—H⋯O hydrogen bonding between the chains.